Investigating College Students’ Views on Mathematics Learning Through Reflective Journal Writing - Ivee Kalalo Guce (Institute of Advanced Engineering and Science, 2017)
The study on reflective journal writing (RJW) and its benefits as assessed by the teachers has long been an inclination in mathematics education. However, little research has been done to explore the feelings of students towards RJW and how such has an effect on their mathematics learning. This study aimed to describe the feelings of the students about RJW. Being a qualitative type of research study, data were acquired through focus group discussion and were analyzed using axial coding. Results revealed that RJW (i) provided opportunities for the students to construct meaning and express personal views and ideas; (ii) built a connection between the teacher and the students; (iii) through the use of prompts, allowed the students to relate mathematics to real-life facts improving their understanding of the subject; (iv) helped the students build association of ideas using their prior knowledge and experiences; and (v) enabled the students to develop self-awareness. The findings suggest that when students are engaged in reflective writing experiences which explicitly promote meaning-making or self-questioning, teachers create an opportunity for them to see how the process of writing can enrich their mathematical learning.